Cybercounseling as one of the skills in the guidance and counseling service in the 21st century - Hidayati Aini; Mudjiran Mudjiran (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2020)
The development of information and communication technology in the 21st century has influenced the guidance and counseling services. Counselors in providing guidance and counseling services can use various ways, new strategies or methods which are innovative to support guidance and counseling services, one of which is by cyber-counseling. cyber-counseling is a professional counseling practice that occurs when clients and counselors are located separately and use electronic media to communicate via the internet. This communication includes the web, email, chat and so on. Therefore, as a professional counselor it is necessary to adapt well in the mastery of information and communication technology to carry out guidance and counseling services. This is an obligation for counselors to implement by utilizing information and communication technology.